2023
DOI: 10.20448/jeelr.v10i2.4490
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of elementary school teachers towards the implementation of the independent curriculum during the COVID-19 pandemic

Abstract: This research aims to explore elementary school teachers' perceptions of implementing an independent curriculum during the COVID-19 pandemic imposed by the Indonesian government as alternative learning to address the problem of learning loss. Data was collected through semi-structured interviews with 38 teachers in primary schools across 13 different regions in Indonesia. Data analysis using thematic qualitative quasi-analysis. The analysis found four main themes: urgency, challenges, support and teaching stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
8

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 27 publications
0
6
0
8
Order By: Relevance
“…The results obtained from prior investigations can be utilised as a benchmark against which to evaluate the findings presented in this paper. While previous research suggests that the implementation of the Merdeka Curriculum in MAN North Sumatra is not substantial (Aliyyah et al, 2023;Imron, 2023;Limiansi et al, 2023), the Islamic Education Teacher of MAN 3 Bukittinggi stated in this discussion that the research findings were quite encouraging, demonstrating that the teachers' adaptation to the Merdeka Curriculum in MAN North Sumatra has advanced. However, it is crucial to acknowledge that certain aspects remain that necessitate enhancement, specifically concerning subject matter innovation.…”
Section: Innovation In Implementing Merdekamentioning
confidence: 67%
See 3 more Smart Citations
“…The results obtained from prior investigations can be utilised as a benchmark against which to evaluate the findings presented in this paper. While previous research suggests that the implementation of the Merdeka Curriculum in MAN North Sumatra is not substantial (Aliyyah et al, 2023;Imron, 2023;Limiansi et al, 2023), the Islamic Education Teacher of MAN 3 Bukittinggi stated in this discussion that the research findings were quite encouraging, demonstrating that the teachers' adaptation to the Merdeka Curriculum in MAN North Sumatra has advanced. However, it is crucial to acknowledge that certain aspects remain that necessitate enhancement, specifically concerning subject matter innovation.…”
Section: Innovation In Implementing Merdekamentioning
confidence: 67%
“…The Ministry of Education, Culture, Research and Technology (Kemdikbudristek) introduced the Merdeka Curriculum in 2022 (Imron, 2023). This curriculum grants teachers the freedom (Limiansi et al, 2023) to design learning experiences that cater to the individual needs and interests of their students (Aliyyah et al, 2023;Imron, 2023). Previous research has shown that the implementation of the Merdeka Curriculum can foster increased motivation (Aliyyah et The Merdeka Curriculum has the potential to inspire teachers to incorporate a wider range of educational approaches (Jonker et al, 2020;Supriyoko et al, 2022), ensuring that students engage in more meaningful learning experiences (Tumin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Positive school cultures built upon positive rapport between teachers, school principals, and students could sustain trust and collaboration for the teacher, which can thrust forward curriculum implementation. Aliyyah et al (2023) [ 65 ] indicated that the effectiveness of the curriculum will mostly depend on the assistance and cooperation of all parties involved. Price, (2011) [ 59 ].…”
Section: Literature Reviewmentioning
confidence: 99%